2012
DOI: 10.1097/aap.0b013e3182475fba
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Regional Anesthesia

Abstract: Trainees became competent in ultrasound needle visualization at a variable rate. This study estimates that novices would require approximately 28 supervised trials with feedback before competency in ultrasound needle visualization is achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(39 citation statements)
references
References 23 publications
1
37
1
Order By: Relevance
“…Quality-compromising behaviors have also been employed in studies investigating the learning curves of skills required for US-guided Regional Anesthesia [7,12]. For the purpose of our trial, we identified 8 behaviors that were applicable to tasks performed on the test phantom models: we used them as outcomes as well as key topics addressed by the instructor during the DL training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quality-compromising behaviors have also been employed in studies investigating the learning curves of skills required for US-guided Regional Anesthesia [7,12]. For the purpose of our trial, we identified 8 behaviors that were applicable to tasks performed on the test phantom models: we used them as outcomes as well as key topics addressed by the instructor during the DL training.…”
Section: Discussionmentioning
confidence: 99%
“…Although deliberate practice models have been described for Regional Anesthesia [6,7], a direct comparison between directed and self-learning has not been carried out. Thus, in this randomized trial, using phantom models, we compared self-and directed learning for the acquisition of IP needle skills in novice operators.…”
Section: Introductionmentioning
confidence: 99%
“…The technique required for ultrasound utilization is certainly user dependent. Obtaining an ideal image of the target structure while maintaining visualization of the needle requires practice and experience [7]. This is particularly true when the target structure is deep and the needle insertion angle is more acute.…”
Section: Ultrasound Versus Conventional Imaging Techniquesmentioning
confidence: 99%
“…Computer-based VR simulation has been utilized effectively for training in a number of procedural domains, e.g. laparoscopic surgery [ 8 ] and colonoscopy [ 9 ]. Grottke et al [ 10 ] have previously described the development of a virtual reality (VR) simulator for regional anesthesia guided by peripheral nerve stimulation.…”
Section: Introductionmentioning
confidence: 99%